Evaluating the impact of COVID-19 pandemic on complicated malaria admissions and outcomes in the paediatric Ho Teaching Hospital of the Volta Region of Ghana. - Verner N Orish; Kennedy Akake; Sylvester Y Lokpo; Precious K Kwadzokpui; Kokou Hefoume Amegan-Aho; Lennox Mac-Ankrah; Emily Boakye-Yiadom; Jamfaru Ibrahim; Theophilus B Kwofie (Public Library of Science (PLoS), 2022)
Since Ghana recorded its first cases of COVID-19 in early March 2020, healthcare delivery in the country has been hugely affected by the pandemic. Malaria continues to be an important public health problem in terms of morbidity and mortality among children, and it is responsible for significant hospital visits and admission. It is likely that, as with other illnesses, the COVID-19 pandemic may have impacted health seeking behaviour, hospital visits, and admissions of malaria among the paediatric population in Ghana. The aim of this study was to evaluate the impact of COVID-19 pandemic on the admissions and outcome of complicated malaria in the Ho Teaching Hospital of the Volta Region of Ghana. The medical records of children admitted for complicated malaria (cerebral and severe malaria) from 2016 to 2020, were obtained from the admission records of the children. Both demographics and clinical details were collected, and data was analysed using SPSS version 25 statistical software. The yearly differences in the trend and proportions of complicated malaria admissions were performed using rate comparison analysis and Pearson chi-square was used to assess the association between the various demographic factors and yearly admission rates. Clopper-Pearson test statistic was employed to determine the 95% confidence intervals of outcome variables of interest. The year 2020 had the lowest admission for complicated malaria (149, 11.5%; 95% CI: 9.7-13.5) but proportionally had, more cases of cerebral malaria (25, 16.8%; 95% CI: 10.9-24.8), and more deaths (6, 4.0%; 95% CI: 1.5-8.8), compared to the years under review. Children admitted in 2020 had the shortest mean stay on admission (4.34 ±2.48, p<0.001). More studies are needed to further elucidate the impact of the COVID-19 pandemic on the health of children in malaria endemic areas.